Effective inhibition of experimental metastasis and prolongation of survival in mice by a potent factor Xa-specific synthetic serine protease inhibitor with weak anticoagulant activity - Banke, Ingo J.; Arlt, Matthias J. E.; Mueller, Markus M.; Sperl, Stefan; Stemberger, Axel; Stürzebecher, Jörg; Amirkhosravi, Ali; Moroder, Luis; Krüger, Achim (Thrombosis and Haemostasis, 2005)
Clinical and experimental evidence suggests that the blood coagulation system is involved in the dissemination of malignant tumors. Consequently, anticoagulant agents have been tested as metastasis suppressors in experimental models. Recently, we have found a close correlation between factor Xa (FXa)-specificity of a series of synthetic serine protease inhibitors and their anti-metastatic potential in a murineT-cell lymphoma metastasis model. Interference of such inhibitors with blood-coagulation may represent a major experimental and clinical obstacle. Here, we test anti-metastatic effects of a recently developed, highly specific 3-amidinophenylalanine-type FXa inhibitor, WX-FX4, with weaker anticoagulant activity when compared to well-established FXa inhibitors, such as DX-9065a, as measured by the activated partial thromboplastin time, prothrombin time, prothrombinase complex activity, and coagulation time. Treatment of mice with WX-FX4 (1.5 mg/kg twice daily) led to significant reduction of experimental liver metastasis of a syngeneic T-cell lymphoma in DBA/2 mice (> 90%), and of experimental lung metastasis of a human fibrosarcoma in CD1 nu/nu mice (> 60%). Due to its relatively low anticoagulant activity, daily treatment over 100 days was possible, leading to significant survival benefits without inducing bleeding anomalities. FXa-inhibitors with highly efficient anti-metastatic potential without coagulationrelated side effects may represent important new tools as anticancer agents.
Keywords: Coagulation Factor Xa inhibitor; metastasis; lymphoma; fibrosarcoma